Temporal trend and factors associated to teenage pregnancy - Lopes, Mislaine Casagrande de Lima; Oliveira, Rosana Rosseto de; Silva, Marcela de Andrade Pereira da; Padovani, Camila; Oliveira, Nelson Luiz Batista de; Higarashi, Ieda Harumi (Revista da Escola de Enfermagem da USP, 2020)
Objective To analyze the trend and factors associated to teenage pregnancy in a municipality in Paraná state. Method Ecological study conducted with registers of babies born to teenage mothers between 2000 and 2015 from the Birth Information System (Sistema de Informação sobre Nascimento). Proportions were calculated year by year for a trend analysis of teenage pregnancy. Two series of three-year periods were collected for an odds ratio analysis of associated factors. Results The following variables were associated to teenage pregnancy: not having a partner; less than eight years of schooling; primiparity; gestational age shorter than thirty-seven weeks; caesarean section; less than seven appointments; and Apgar below seven in the first minute. A decline trend was observed among pregnant teenagers who had partners; growing trend for teenage expectant mothers who had more than eight years of schooling and premature birth; decline/growing for normal birth; growing for number of prenatal appointments; decline for first and fifth minute Apgar score; growing for congenital anomalies. Conclusion The analysis provided information that can be used to promote pregnancy prevention strategies and assistance to adolescent mothers.